Laparoscopic vs open surgery for colorectal cancer patients with high American Society of Anesthesiologists classes. Issue 3 (18th December 2019) - Fukuoka, Eiji; Matsuda, Takeru; Hasegawa, Hiroshi; Yamashita, Kimihiro; Arimoto, Akira; Takiguchi, Gosuke; Yamamoto, Masashi; Kanaji, Shingo; Oshikiri, Taro; Nakamura, Tetsu; Suzuki, Satoshi; Kakeji, Yoshihiro
Abstract: Introduction: Laparoscopic surgery has become popular for colorectal cancer treatment in recent years. However, its success rate even among high‐risk patients remains debatable. The present study aims to compare the short‐ and long‐term outcomes between laparoscopic and open surgeries in the American Society of Anesthesiologists (ASA) classes 3 and 4 patients with colorectal cancer. Methods: This was a single‐center, retrospective, cohort study performed at a university hospital, with 78 patients suffering from colorectal cancer who underwent surgery in ASA classes 3 and 4 as respondents. Patient and tumor characteristics, operative outcomes, and prognoses were factors compared between the open and laparoscopic groups. Results: Compared with the open group, laparoscopic group had longer operation time (median 287.5 vs 204.5 minutes, P = .001), less operative blood loss (median 40 vs 240 mL, P = .020), and fewer postoperative complications (24% vs 55%, P = .011). In addition, operative approach (open vs laparoscopic) served as an independent factor for the occurrence of postoperative complications [HR = 3.963 (1.344‐12.269), P = .013]. In terms of overall survival and recurrence‐free survival ( P = .171 and .087, respectively), no significant difference was found between the two groups. Conclusion: Laparoscopic surgery is thus associated with more favorable short‐time outcomes and could be adopted as treatment even for colorectal cancer ASA class 3 and 4 patients.